Adjuvant radiotherapy for early head and neck squamous cell carcinoma with perineural invasion: A systematic review. (28th November 2015) - Bur, Andrés M.; Lin, Alexander; Weinstein, Gregory S.
ABSTRACT: Perineural invasion (PNI) is widely regarded as a negative prognostic factor in head and neck squamous cell carcinoma (HNSCC). Treatment guidelines recommend adjuvant radiotherapy (RT) for patients with adverse pathologic features, including PNI. The purpose of this study was to systematically review the literature to determine if patients with PNI as their only indication for adjuvant therapy benefit from adjuvant RT. In total, 339 abstracts were reviewed for relevance leaving 85 articles, which were evaluated in detail. Thirteen retrospective studies addressed the role of adjuvant RT for patients with PNI. Evidence is lacking to recommend adjuvant RT for all patients with HNSCC with PNI. However, the literature suggests that large nerve or multifocal PNI may predict worse outcome and may be a more appropriate indication for adjuvant therapy. We advocate that patients decide whether to undergo adjuvant therapy after a discussion of the limitations of current evidence. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E2350–E2357, 2016